413 Effect of chitosan inclusion and dietary crude protein level on rumen fermentation in beef heifers fed a total mixed ration. (5th December 2019) - Kirwan, Stuart; Boland, Tommy; Serra, Eleonora; Rajauria, Gaurav; Pierce, Karina
Abstract: Chitosan (N-acetyl-D-glucosamine polymer) is a natural biopolymer, which is the second most abundant organic compound on earth, found in lower plants and some arthropods and crustaceans. Studies with ruminants have shown that supplementing with chitosan can alter ruminal fermentation, including higher propionate concentration and lower acetate to propionate ratio, improving the energy efficiency within the rumen though data on nitrogen metabolism is lacking. Therefore, the objective of this study was to evaluate the effects of chitosan with different dietary crude protein (CP) inclusion on rumen fermentation in beef heifers. Eight ruminally cannulated Belgian Blue x Holstein Friesian heifers (752 ± 52Kg BW) were allocated one of four dietary treatments in a 2 x 2 factorial Latin Square design (n = 8). Diets were offered as total mixed ration (TMR) consisting of grass silage plus concentrate. Diets were offered once daily ad libitum. Dietary treatments were as follows: high CP (16%) +/- chitosan (10g kg-1 DMI) supplementation (HP+) or (HP-) and low CP (12%) +/- chitosan supplementation (LP+) or (LP-). Experimental periods were 25d in duration (14 d dietary adaptation and 10 d sampling). Rumen fluid was collected via cannula every 2 h post feeding for analysis of ruminal pH, ammonia (NH3) and volatile fatty acids (VFA) over a 48-hour period. Data was analysed using Proc Mixed procedure in SAS. Significant differences were considered when P < 0.05. Dietary treatment had no effect on ruminal pH (P > 0.05). Chitosan supplementation had no effect on ruminal NH3 and VFA concentrations (P > 0.05), whereas, animals offered 16% CP had higher concentrations of ruminal NH3 (P < 0.001). In conclusion, supplementing a TMR diet fed to beef heifers with chitosan had no effect on rumen fermentation. However, reducing dietary CP concentration fed to beef animals resulted in lower rumen NH3 concentrations.